Nanocrystalline graphite nanopores for DNA sensing. (May 2021) - Wang, Yunjiao; Cheng, Min; Wang, Liang; Zhou, Daming; He, Shixuan; Liang, Liyuan; Zhang, Feng; Liu, Chang; Wang, Deqiang; Yuan, Jiahu
Abstract: Free-standing nanocrystalline graphite (NCG) membranes directly grew on SiNx substrates with the aid of the catalyst-free chemical vapor deposition method. A new type of NCG nanopore was formed in the NCG membrane via controlled dielectric breakdown in KCl electrolyte. The electrical properties, especially the ionic conductance of the NCG nanoporewere examined under different physical parameters (pore size, ion strength, and pH condition). Due to their impressive transport properties, we first realized DNA sensing using the NCG nanopores. Graphical abstract: Image 1 Highlights: A nanopore was formed in a free-standing nanocrystalline graphite 2D membrane via controlled dielectric breakdown. Nonlinear but symmetric I–V curves of the NCG nanopore indicate the existence of internal electrostatic potential. DNA translocation caused stochastic upward current pulses. The dsDNA translocation speed was slowed down compared to other nanopores.